The Lipid Intensive Drug Therapy for Sepsis Phase II Pilot Clinical Trial - Guirgis, Faheem W; Black, Lauren Page; Henson, Morgan; Bertrand, Andrew; DeVos, Elizabeth; Ferreira, Jason; Gao, Hanzhi; Wu, Samuel S; Leeuwenburgh, Christiaan; Moldawer, Lyle; Moore, Frederick; Reddy, Srinivasa T (Critical care medicine, 2024)
Low cholesterol levels in early sepsis patients are associated with mortality. We sought to test if IV lipid emulsion administration to sepsis patients with low cholesterol levels would prevent a decline or increase total cholesterol levels at 48 hours. Phase II, adaptive, randomized pilot clinical trial powered for 48 patients. Emergency department or ICU of an academic medical center. Sepsis patients (first 24 hr) with Sequential Organ Failure Assessment greater than or equal to 4 or shock. Patients meeting study criteria, including screening total cholesterol levels less than or equal to 100 mg/dL or high-density lipoprotein cholesterol (HDL-C) + low-density lipoprotein cholesterol (LDL-C) less than or equal to 70 mg/dL, were randomized to receive one of three doses of lipid emulsion administered twice in 48 hours or no drug (controls). The primary endpoint was a change in serum total cholesterol (48 hr - enrollment) between groups. Forty-nine patients were enrolled and randomized. Two patients randomized to lipid emulsion were withdrawn before drug administration. Data for 24 control patients and 23 lipid emulsion patients were analyzed. The mean change in total cholesterol from enrollment to 48 hours was not different between groups and was 5 mg/dL ( sd 20) for lipid emulsion patients, and 2 mg/dL ( sd 18) for control patients ( p = 0.62). The mean changes in HDL-C and LDL-C were similar between groups. Mean change in triglycerides was elevated in lipid emulsion patients (61 mg/dL, sd 87) compared with controls (20 mg/dL, sd 70, p = 0.086). The 48-hour change in SOFA score was -2 (interquartile range [IQR] -4, -1) for control patients and -2 (IQR -3, 0) for lipid emulsion patients ( p = 0.46). Administration of IV lipid emulsion to early sepsis patients with low cholesterol levels did not influence change in cholesterol levels from enrollment to 48 hours.